Zainudin MZ's Contribution of Da’wah in Forming Political Awareness in Indonesia - Mastori; Iman, Sunardi Bashri; Falhan, Ahmad; Maskur, Asep; MisbaCh, Wahyu; Arifin, Zenal (Fakultas Dakwah UIN Saizu Purwokerto, 2025)
This study examines the contribution of Zainudin MZ's da'wah in shaping the political awareness of the Indonesian people. Zainudin MZ, known as a 'da'I for a million people', is popular because of his strong and communicative rhetoric and his courage in bringing socio-political messages in his da'wah. This approach makes da'wah a means of social transformation that can foster political awareness of the people, especially in the context of the transition of the Indonesian government from the New Order era to the reformation. This study uses a descriptive qualitative approach with a literature study method and analysis of Zainudin MZ's da'wah discourse in the form of lectures, books, and mass media documentation. The study results show that Zainudin MZ has contributed to integrating da'wah with social, political, and power issues. Consistently, he voices the values ​​of justice, honesty, and concern for the ordinary people from the perspective of the da'wah language, which is easily understood by the wider community. His involvement in practical politics during the Reformation also shows a form of courage to make da'wah an instrument of structural change. Ultimately, he chose to return to the path of cultural da'wah because of his disappointment with less-than-ideal political practices. This finding strengthens the importance of the role of da'wah as a medium to shape the political awareness of society within the framework of Islamic teachings.